The Role of Unmanned Aerial Vehicles (UAVs) in Indonesian Air Defense Management - Shafira Karunia Hildawati; Susilo Adi Purwantoro; Editha Praditya Duarte; Fachmi Khoiruddin; Hikmat Zakky Almubaroq (CV. AFDIFAL MAJU BERKAH, 2024)
Indonesia is an archipelagic state with land and maritime borders with other nations. The use of Unmanned Aerial Vehicles (UAVs) has become crucial in safeguarding Indonesia's defense and border areas. This research employs a qualitative method, aiming to gain a deep understanding of the role of UAVs in the Defense management of Indonesia's, covering complex aspects such as policies, implementation, and their impact. The findings reveal that sustained investment in UAV technology and infrastructure is essential to strengthen Indonesia's air defense capabilities. Particularly, High-Altitude Long Endurance (HALE) UAVs prove to be effective and reliable in surveillance with their ability to operate at high altitudes and for extended durations. In the context of Indonesia's air defense, UAVs significantly enhance surveillance, reconnaissance, and national security. Effective integration and utilization of UAVs are key to maintaining protection and sovereignty over the airspace. Appropriate regulations and the establishment of ownership registries are crucial to support responsible UAV usage, especially concerning national security and counterterrorism. The evolving significance of UAVs will continue to shape defense paradigms in the future.